Measuring Multifactor Productivity Growth - Wölfl, Anita (OECD Publishing, 2007)
This paper quantifies and examines the contribution of capital, labour and multifactor productivity (MFP) to GDP growth and analyses the role of measurement of capital and labour inputs for the MFP estimate, using a comprehensive growth accounting exercise for 14 OECD countries. For most OECD countries, the strongest contributions to GDP growth over the past decade have come from growth in total capital input and MFP. This is to some extent related to an increasing role of information and telecommunication technologies in economic growth, particularly over the 1995-2003 period. The importance of measurement issues varies substantially with the type of measurement issue being considered. Substantial differences are observed between employment and hours worked based MFP growth rates. Also, the respective weights with which capital and labour enter the growth accounting equation, and thus, the assumptions concerning the efficiency of production and competition in product markets, significantly influence the resulting MFP estimate. Finally, the results suggest that policy conclusions on the basis of different empirical studies should be made very carefully, in particular as regards the time period for which the respective studies have been undertaken, as well as whether actual or trended time series are being considered
Keywords: Science and Technology